Prevalence and clinical impact of major incidental findings detected on routine cardiovascular resonance imaging prior to catheter ablation of atrial fibrillation. (19th May 2022) - Richter, S; Ebert, M; Karrengarn, R; Oebel, S; Doering, M; Kircher, S; Jahnke, C; Hindricks, G; Paetsch, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Preprocedural contrast-enhanced cardiovascular magnetic resonance (CMR) or computed tomography (CT) imaging of the left atrium (LA) and pulmonary veins (PVs) is usually employed to facilitate catheter mapping and ablation of atrial fibrillation (AF). Incidental findings (IFs) are common on cardiac imaging prior to AF catheter ablation (AFCA). However, previous studies were of small size and have mainly focused on radiological extracardiac IFs detected on preprocedural CT scan. Purpose: To assess the prevalence of major cardiac and extracardiac IFs on routine preprocedural CMR in a large cohort of consecutive patients scheduled for first-time AFCA, and to report its impact on clinical decision-making and management. Methods: All consecutive patients who underwent routine preprocedural CMR prior to first-time AFCA between April 2015 and March 2019 were considered for analysis. Main exclusion criteria were referral for repeat AFCA; prior cardiac CT or CMR imaging; and general contraindication to CMR or AFCA. All CMR examinations consisted of survey images with full thoracic coverage, cardiac cine and late-gadolinium enhancement imaging, and three-dimensional contrast-enhanced CMR angiography of the LA/PVs. An IF was defined as major when any newly detected finding either resulted in cancellation of the AFCA procedure or intentional deviation from the standard AFCA protocol. In patients with accessory or anomalous PVs the ablation strategy was individually tailored aiming at isolation of all PVs. Results: Two thousand consecutive patients (62±10 years; 59% male) with paroxysmal (48%) or persistent (52%) AF were included. Among the entire study cohort 172 patients (8.6%) had a total of 184 cardiac (75%) and extracardiac (25%) major IFs (Fig. A+B). Preprocedural detection of a major IF resulted in cancellation of the scheduled AFCA procedure in 88 patients (4.4%). Forty-two patients (2.1%) have thereupon never been ablated, 46 patients (2.3%) underwent postponed AFCA after a median time from CMR imaging of 83 (32-213) days. The remaining 84 patients with major IF (4.2%) underwent an individualized approach to AFCA (Fig. A). The most common major IFs were accessory or anomalous PVs in 76 (3.8%), extracardiac abnormalities suspicious of malignancy in 29 (1.5%), and positive stress perfusion imaging in 19 (1.0% overall; 7.2% of 261 tested) patients. In 19 patients (1.0%) preprocedural CMR detected a previously unknown intracardiac thrombus or structural cardiac disease. Conclusion: Unexpected major IFs on routine preprocedural CMR affected clinical decision-making and therapeutic management in 8.6% of patients scheduled for first-time AFCA at our institution. Whether preprocedural CMR imaging may improve safety and outcome of AFCA needs to be addressed in future research.